Pemetaan Tingkat Kebisingan Di Pabrik Pusri 1B PT. Pupuk Sriwidjaja Palembang Dengan Metode Noise Mapping - Nabil Abidin; Aryo Sasmita; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
PT. Pupuk Sriwidjaja in its operational activities has the potential to generate noise coming from urea fertilizer production Workers who are constantly exposed to noise have the potential to affect workers' health and comfort. The purpose of this research is to know the intensity of noise generated by urea fertilizer production machine, exposure time, map of noise distribution pattern, and noise control effort. The noise measurement method refers to the noise mapping method and the tool used is the Sound Level Meter (SLM). Measurement based on the noise mapping method is done for 1 day. The results showed that from 115 points of measurement, there were 2 points showing numbers that exceeded the quality standard. The highest noise level is 86.6 dB where it is very close to the noisy source, and the lowest noise level is 65 Db which is far enough from the noisy source. Based on the calculation using NIOSH formula from 115 point of noise mapping method, there are 113 dots showing exposure time above NIOSH recommended standard. The highest noise level was 86,6 dB with a duration of 5,1 hours and the lowest noise level was 65 dB with a duration of 8000 hours. Sound mapping using the Surfer 13 program to find out the pattern of noise distribution caused by the noise mapping method. Based on the results of Surfer 13 shown by different colors of blue purple green yellow orange and red. The planned noise control measures are by engineering control, adminstrative control, and control on the recipient or worker.Keywords: Noise, NIOSH, Noise Mapping, Surfer 13, Pupuk Sriwidjaja Palembang